Dissociable contributions of amygdala and hippocampus to emotion and memory in patients with Alzheimer's disease. Issue 6 (12th December 2015) - Guzmán‐Vélez, Edmarie; Warren, David E.; Feinstein, Justin S.; Bruss, Joel; Tranel, Daniel
Abstract: The amygdala and the hippocampus are associated with emotional processing and declarative memory, respectively. Studies have shown that patients with bilateral hippocampal damage caused by anoxia/ischemia, and patients with probable Alzheimer's disease (AD), can experience emotions for prolonged periods of time, even when they cannot remember what caused the emotion in the first place (Feinstein et al. (2010) Proc Natl Acad Sci USA 107:7674‐7679; Guzmán‐Vélez et al. (2014) Cogn Behav Neurol 27:117‐129). This study aimed to investigate, for the first time, the roles of the amygdala and hippocampus in the dissociation between feelings of emotion and declarative memory for emotion‐inducing events in patients with AD. Individuals with probable AD ( N  = 12) and age‐matched healthy comparisons participants (HCP; N  = 12) completed a high‐resolution (0.44 × 0.44 × 0.80 mm) T2‐weighted structural MR scan of the medial temporal lobe. Each of these individuals also completed two separate emotion induction procedures (sadness and happiness) using film clips. We collected real‐time emotion ratings at baseline and multiple times postinduction, and administered a test of declarative memory shortly after each induction. Consistent with previous research, hippocampal volume was significantly smaller in patients with AD compared with HCP, and was positively correlated with memory for the film clips. Sustained feelings of emotion and amygdala volume did not significantly differ between patients with AD and HCP. Follow‐up analyses showed a significant negative correlation between amygdala volume and sustained sadness, and a significant positive correlation between amygdala volume and sustained happiness. Our findings suggest that the amygdala is important for regulating and sustaining an emotion independent of hippocampal function and declarative memory for the emotion‐inducing event. © 2015 Wiley Periodicals, Inc.